Exploring the influence of ‘Korean Wave’ on brand loyalty: The moderating role of product type - Lady, Lady; Meilani, Lara; Cuandra, Fendy; Na, Bai (Asian Management and Business Review, 2024)
The ‘Korean Wave’ has significantly impacted the global economy, especially in Indonesia. However, there is a gap in understanding how Korean celebrities, as brand ambassadors, influence local consumer behavior and purchase intentions. This study aims to clarify this impact using the theory of planned behavior (TPB) framework. The roles of brand attachment, brand love, and brand loyalty, moderated by product type, were examined with 194 survey respondents, and data was analyzed using SmartPLS software. Key findings indicate that brand personality significantly influences brand attachment. Customer brand engagement positively affects brand love. Brand attachment impacts both brand loyalty and brand love, while brand love strongly influences brand loyalty. Brand loyalty significantly affects purchase intentions, confirming that loyal customers are more likely to make repeat purchases. Product type only moderates the influence of brand attachment on brand loyalty, not the influence of brand love on brand loyalty. The implications for marketers are significant. Businesses should leverage Korean celebrities as brand ambassadors to enhance brand visibility and loyalty. Aligning brand personality with ambassadors can deepen consumer attachment. Creating engaging content and focusing on emotional branding can foster stronger connections. Tailoring marketing strategies to different product types and monitoring brand loyalty feedback can enhance market performance. Despite its contributions, the study acknowledges limitations, including potential demographic biases and the need for broader cultural and product category exploration in future research.